Designing, Implementing, and Evaluating: Management of Teaching the Kitab kuning in Pesantren - Ja'far, Ja’far (Jurnal Inovatif Manajemen Pendidikan Islam, 2025)
The teaching and learning of kitab kuning in pesantren remains a fundamental tradition, yet its management and evaluation process often lack systematic structure, affecting the effectiveness of pesantren’s educational outcomes. This research aims to analyze the planning, implementation, and evaluation of kitab kuning learning at Pondok Pesantren Nurul Qodim Al-Mansuriyah Taman Sari Pasuruan. This qualitative case study involved direct observation, interviews, and documentation analysis. The results indicate that the pesantren’s management of kitab kuning learning has been well-organized, with collaborative planning, effective teaching methods such as bandongan, and continuous evaluation through tests and daily monitoring. The evaluation methods include scheduled exams (written, oral, and reading tests) as well as non-test assessments like teacher observation during lessons. This integrated approach supports sustained improvement in teaching quality and student mastery, contributing to upholding the pesantren’s tradition of classical Islamic studies while adapting to modern educational standards.